(untitled) (Baghdad Science Journal, 2008)
Indole acetic acid (IAA) produced from F. oxysporum (F2) was purified by several steps included extraction by cold ethyl acetate ; Column chromatography using silica gel and TLC chromatography . The pure indole acetic acid (IAA) which produce by F. oxysporum (IAA) was tested by ultraviolet spectra at (200-300)nm ; and appear that the maximum absorbance at 229nm , the high performance liquid chromatography (HPLC) used to test the purity of the indole acetic acid and the results showed one peak at appearance time 3.822 min